Entry in a Cournot Market - Frank, Charles R. (Review of Economic Studies, 1965)
Journal Article Entry in a Cournot Market Get access Charles R. Frank, Jr. Charles R. Frank, Jr. East African Institute of Social Research and Makerere University College Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 3, July 1965, Pages 245–250, https://doi.org/10.2307/2295829 Published: 01 July 1965